Analisis Tingkat Kebutuhan Abraham Maslow Pada Tokoh Utama Kinara Dalam Novel Primerose Karya PenieJingga 02 - Fadila Khairun Nisa; Riskika Sri Utami; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to describe the level of needs of the main character Kinara in the novel entitled Primerose by PenieJingga02. The problem raised in this research is how the character Kinara is able to fulfill Maslow's five levels of needs and whether Kinara is able to achieve the need for self-actualization at the highest level of Maslow's needs. The method used in the research is a descriptive qualitative literary psychology approach. literary psychology approach using the study of Abraham Maslow's humanistic theory. Maslow's five levels of needs that will be analyzed in the character Kinara are the psychological needs (physiological needs), the safety needs (needs for security), the belonging and love (needs for affection), the esteem needs (self-esteem needs) , the actualitation needs (actualization needs). This research shows that the main character Kinara has not been able to actualize herself because of the five needs there are two needs that have not been fulfilled, so the character Kinara has not been able to fulfill the last need, namely self-actualization.